Volar perforators of common digital arteries: an anatomical study. (March 2015) - Gasiunas, V.; Valbuena, S.; Valenti, P.; Le Viet, D.
The palmar triangle is an area vascularized by perforator arteries arising from the common digital palmar arteries. The aim of this article was to perform an anatomical study of common digital palmar arteries perforators. Twelve injected specimens were included in this study. The purpose was to quantify the number of perforator arteries of each common digital palmar arteries in the 2nd, 3rd, and 4th intermetacarpal space, measure distances between them, between the distal perforator and corresponding commissure, and the distance between the proximal perforator and the superficial palmar arch. Four to eight perforators were arising from common digital palmar arteries of the 2nd, 3rd, and 4th intermetacarpal space. The average distance between perforator arteries was 6.5 mm, between superficial palmar arch and proximal perforator artery – 8.2 mm, between the distal perforator artery and corresponding commissure – 6.3 mm.